2017
DOI: 10.1021/jacs.6b12374
|View full text |Cite
|
Sign up to set email alerts
|

Pursuit of Record Breaking Energy Barriers: A Study of Magnetic Axiality in Diamide Ligated DyIII Single-Molecule Magnets

Abstract: Dy III single-ion magnets (SIMs) with strong axial donors and weak equatorial ligands have recently been sought after as model systems with which to harness the maximum magnetic anisotropy of Dy III ions. Utilizing a rigid ferrocene diamide ligand (NN TBS ), a Dy III SIM, (NN TBS )DyI(THF)2, 1-Dy (NN TBS = fc(NHSitBuMe2)2, fc = 1,1' ferrocenediyl), composed of a near linear arrangement of donor atoms, exhibits a large energy barrier to spin reversal (770.8 K) and magnetic blocking (14 K). The effects of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(123 citation statements)
references
References 32 publications
1
121
0
Order By: Relevance
“…Low‐temperature magnetisation studies also show a distinction between 1 and the other compounds (insets in Figures S1–S11 in the Supporting Information). Compound 1 shows a simple increase in M ( H ) at 2, 5 and 10 K, whereas 2 – 11 show S‐shaped curves at 2 K, suggesting significant memory effects . These S‐shaped curves cannot be reproduced by our CASSCF calculations because they arise from the confluence of the field dependence of the relaxation rates (not studied here, see ref.…”
Section: Resultsmentioning
confidence: 84%
“…Low‐temperature magnetisation studies also show a distinction between 1 and the other compounds (insets in Figures S1–S11 in the Supporting Information). Compound 1 shows a simple increase in M ( H ) at 2, 5 and 10 K, whereas 2 – 11 show S‐shaped curves at 2 K, suggesting significant memory effects . These S‐shaped curves cannot be reproduced by our CASSCF calculations because they arise from the confluence of the field dependence of the relaxation rates (not studied here, see ref.…”
Section: Resultsmentioning
confidence: 84%
“…where q i , p i , and Q i are the charge, dipole moment, and quadrupole moment, respectively, of the i th atom of the ligand, whereas r i is the position vector of the i th atom. All the charges and moments are extracted from ab initio calculations (see above) followed by a LOPROP analysis of the electronic density. It is important to stress that this method is an analysis of the results of calculations done with high level of theory and therefore it does not have any prediction power by itself.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, high‐performance lanthanide SMMs possess highly symmetric electrostatic environments that induce strong stabilization of the magnetic ground state . A striking illustration of the latter concept is given by the Ln–phthalocyanine (LnPc) systems, where the organic ligands impose a strict D 4 d site symmetry to the lanthanide ion and dramatically improve its magnetic properties when compared with a distorted coordination environment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] Most of these studies focusingo nc orrelations between crystal packing, polymorphism,a nd optical properties are foundw ithin the field of p-conjugated materials foro ptoelectronicd evices, that is, organic light-emitting diodes (OLEDs), organic thin-filmt ransistors, waveguides,r esonators or solar devices.A lternatively, photoluminescent lanthanide (Ln)-based molecules and materials are highly attractive candidates for opto-magnetic applications spanning the broad range from optical sensors, biomedical probesa nd contrast agents to waveguides, and single-molecule magnets, to name af ew. [11][12][13][14][15][16][17][18][19][20][21][22][23] While significant effect of crystal packing on the optical properties of Ln 3 + -based materials has been shown for coordi-nationp olymers and metal-organicframeworks (MOFs), surprisinglyt his has not yet been exploited in molecular species that exhibit polymorphism. [24][25][26][27][28][29] It has been demonstrated that the ligand sphereo ft he Ln 3 + centers plays an important role with respect to molecular geometry and arrangement ultimately influencing the photoluminescence (PL) behavior.…”
Section: Introductionmentioning
confidence: 99%